PERANAN PENYELENGGARAAN UPT LK WILAYAH I TERHADAP KUALITAS TENAGA KERJA KOTA PEKANBARU ( Studi kasus Workshop Listrik) - Efri Efri; Harlen Harlen; Maulida Yusni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The purpose of this study was to determine the role of UPT LK region I in the quality of workforce in Pekanbaru City (case study of electricity workshop). The population in this study were participants who attended an electric vocational training in UPT-LK region 1 Pekanbaru from 2014-2018 with a population of 513 participants. The sample was taken randomly (random sampling) as many as 84 respondents. The type of data used are primary and secondary data, while data collection techniques use questionnaires and interviews. Data analysis method used in this research is descriptive analysis. The results of the workforce research coming from UPT LK Region I Pekanbaru have a job suitability with their expertise, then the workforce has technical ability, work discipline, and good morale, the workforce works in accordance with their expertise, and the workforce has a good quality of work compared another.Keywords: Role, quality, labor